Metodología del trabajo colaborativo en el área de lengua y literatura: Cuarto año de educación básica - Flores Verdezoto, Katty Lorena (2023)
Knowledge is acquired through interaction with the cultural and social environment, so promoting collaboration and social interaction is a successful practice to achieve meaningful learning. The objective is to propose a system of activities for collaborative work in Language and Literature in the fourth year of basic education of the "Gutberto García" Basic Education school. Theoretical research methods associated with collaborative work, the constructivist approach and in particular for teaching in the area of Language and Literature are applied. A diagnosis is applied with the use of empirical methods: observation, documentary review, interview with selected students and survey of the ten teachers involved (checking its validity and reliability with the application of the Cronbach's Alpha tests with the SPSS software version 25) which results in demonstrating the existing shortcomings in the teaching-learning process and the need to propose a system of activities. After the application of the system of activities, the advances in terms of academic results and a greater development of basic and social-citizen skills are demonstrated; as well as through the application of the Iadov and Net Promoters Indices the perception of teachers regarding the applicability, ease of use and recommendability of the proposal made.